Inclusão de levedura hidrolisada e levedura seca na dieta de leitões recém-desmamados - Oliveira, Millene Torres de (2012)
This research was conducted in order to evaluate the performance and intestinal microbiota of piglets at 25 days, consuming dry yeast (LS) and hydrolyzed (LH) in the diet. The 108 pigs were weaned at 25 days, and housed in 24 pens, with six animals per cage and subjected to two experiments which were: Experiment 1: 25-49 days old piglets, and they were fed three treatments: T1 (negative control), T2 (0.02% LH) and T3 (0.01% LH). Experiment 2: piglets of 50-72 days of age, with three treatments which were: T1 (Negative Control), T2 (0.005% of LH) and T3 (0.025% LS) of. The performance parameters evaluated were weight gain (WG), feed conversion (FC) and feed intake (FI). Fecal samples were performed on day zero (one day before starting the experiment) at 49 and 72 days of age of the animals. A pool of sample per pen was collected, which were subjected to microbiological tests in order to account for the formation of gram-negative colonies. Data were analyzed using general linear models procedure for the analysis of variance (ANOVA) with treatment and block included in the experimental model. Variables that had significant effect on the F-test were compared by using the Method of Least Squares (lsmeans) of SAS (1996), and treatment effects were considered significant at P<0.05. Microbiological data of gramnegative bacterial counts were converted to a logarithmic scale on the base 10. Correlations between variables were made using the Pearson correlation procedure. Results were considered significant at P<0.05. There was no statistical difference between treatments for all the performance parameters analised (P>0.05). Microbiological analyzes showed no significant results in all treatments in both experiments (P> 0.05). In the experiments, yeast supplementation showed no change on performance of piglets, and on colony count of Gram-negative bacteria in the fecal samples.